An Overview of Alternative Treatments for the Healing Rate of Fracture Patients in Bulukumba Regency - Alfira, Nadia; Harida Asripa; Amirullah; A. Nurlaela Amin (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2025)
Background : Fractures (broken bones) are the most common occurrence in the productive age group. According to WHO, in 2020, fractures were recorded in around 13 million people with a prevalence of 2.7 % . Fractures are one of the causes of disability caused by trauma, namely accidents. Fractures can cause disability or even death if the fracture is not handled properly. Medical treatment of fractures is not the only option for people today. Objective : To find out the picture of alternative treatments on the healing rate of fracture patients in Bulukumba Regency. Method : This study used a qualitative research design with a descriptive-survey approach. Six participants were selected according to the criteria and subjected to observations and interviews. Research result : The research results identified three themes, namely: (1) alternative medicine with the subthemes of alternative medicine therapists and forms of alternative medicine, (2) healing rate with the subthemes of fracture treatment, duration of treatment and fracture condition, (3) Coping mechanisms with the subthemes of understanding alternative medicine, perceptions of alternative fracture treatment, reasons for choosing alternative fracture treatment. Conclusion and Recommendations : Alternative medicine therapists are often referred to as sanro or shamans in the community. Alternative treatments for fractures include massaging with oil, reciting prayers , and wrapping the fracture in cardboard. Reasons for choosing alternative medicine for fracture management vary, including low cost, faster healing, encouragement from family or parents, and proximity to alternative treatment facilities. The type of fracture experienced by patients who come for treatment with alternative medicine is a closed fracture. There are some whose fractures have not healed, but there are also some whose have healed. Researchers suggest that further research in the future could delve deeper into alternative fracture treatments for patients undergoing alternative fracture treatments. Keywords :​ fracture, alternative medicine, healing rate